The Impact of Differentiated Instruction on the Acquisition of Short Stories by High School ESL Learners in an American School in the UAE - AL RWAIS, SALEH YOUSEF (2023)
Abstract This study was conducted to examine the impact of Differentiated Instruction on the acquisition of short stories by high ESL learners in an American school in the UAE. To achieve the objective of this study, a quasi-experimental design was used, in which pre- and post-tests were administered to two groups of participants, a control group and an experimental group. A traditional instructional approach was used in the control group, whereas differentiated instruction was used in the experimental group. Using the t-test, a statistical analysis was carried out on the results of the study. In light of the higher scores achieved by the experimental group as compared to the control group, it can be concluded that differentiated instruction is a worthwhile approach. Through the use of Differentiated Instruction, this study will contribute to the existing body of literature concerning the teaching of short stories and will thereby enhance the literary skills of students. As a final point, additional research should be conducted to examine the impact of differentiated instruction on the acquisition of different literary genres.